The coronavirus pandemic impact on India's Yoga tourism business - H R Dayananda Swamy; Govindasamy Agoramoorthy (Wolters Kluwer Medknow Publications, 2021)
Yoga tourism is an emerging market in India, with a great economic potential to boost revenue in the wellness travel and hospitality industries. Millions of tourists from foreign countries visit India each year to explore the history, philosophy, practice, and experiences of Yoga as the art originated there. However, little is known in the scientific literature on the Yoga-linked tourism and hospitality subject. Besides, how the enduring COVID-19 pandemic impacts the emerging Yoga tourism and hospitality sector in India is not fully understood. This article highlights the less-known aspects of India's Yoga tourism and hospitality and how the continuing COVID-19 pandemic impacts the business.